Zmiany na rynku bankowości hipotecznej w Polsce - ewolucja czy rewolucja? - Szelągowska, Anna (Changes in Polish mortgage banking market - evolution or revolution?, 2006)
The development of mortgage banking in Poland is proceeding in two stages. The first stage of evolution was in a period 1872-1948, the second has started in 1997. However, if we compare our mortgage market with the other EU mortgage markets, in Poland we haven't to deal with a revolution but with an evolution in mortgage banking system. Mortgage banks don't evolve in Polish financial market, because there's no sign that in next few years the mortgage banks will be working at full speed. The role of mortgage banks is getting smaller by the year.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1141, s. 310-315